Developing Mathematical Reasoning Skills through Classroom Questions: A Framework based on Problem-Chain Teaching - Wan Yan (IKIP Siliwangi, 2026)
Mathematical reasoning is a core competency in compulsory education mathematics curricula worldwide, yet classroom practices frequently fall short in systematically cultivating this ability. Students often rely on mechanical problem-solving techniques rather than engaging in sustained reasoning processes. This study addresses the critical research gap concerning how problem-chain teaching can serve as an effective instructional paradigm for developing students' mathematical reasoning skills. Using a conceptual synthesis methodology that integrates domestic and international literature on mathematics pedagogy, classroom questioning, and reasoning development, this paper analyzes the mechanisms through which classroom questioning supports reasoning and proposes three differentiated pathways: problem-chain design strategies (analogical, inductive, and deductive chains), optimization of oral questioning types, and organization of reasoning discourse through student work samples. The framework provides mathematics teachers with systematic, operable strategies that align with curriculum standards and support progressive reasoning development from primary through secondary levels. Key contributions include: (1) the cross-cultural integration of Eastern and Western research traditions on reasoning and questioning; (2) a three-level reasoning progression model that guides differentiated problem-chain and questioning design; and (3) actionable teaching recommendations grounded in empirical evidence from classroom studies conducted in diverse educational contexts (Kapur, 2016; Brodie, 2010).